Rupat Beach Theme Park Dengan Pendekatan Arsitektur Post Modern - Pastiche - Harian Syah; Pedia Aldy; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Rupat Beach Theme Park is a medium beach recreation forum in the Rupat subdistrict, which has function as a family holiday place, specially for Riau society and the regional around it. Geographically, the position of Rupat Island is very strategic, because it is located between the international trade route. This island is also located between two important place, they are Bandarkuna Malaka in the east side, and Sumatera Island as the place which produce various nature properties in the west side. This design use the part of the post modern architecture as a theme, this is metaphor, and the concept is pastiche, whichis the intend of this concept is to move one element (atmosphere, decorative manner, building mass form ), or a group of element from a place to the other. In this design there are some element which be moved, which come from 5 country in the south east Asia (Cambodia, Malaysia, Thailand, Singapore, and Indonesia), from each country, we take one or two part which will be pastiche-ly. The conclusion which we get from this design of Rupat Beach Theme Park are: Giving the clear limit from each zone based on function which have beendetermined, balancing the position of games forum and the building function, and the application of pastiche concept which has been applied on each of building mass.Keywords: Rupat Beach Theme Park, Post-modern Architechture, Methapor, Pastiche, Recreation Forum, Beach.